Against the ‘poetry of bourgeois mourning’? Lyricism and criticism in Ann Cotten (Configurazioni. Research on contemporary poetry, 2024)
This article aims to reflect on the relationship between lyricism and criticism in Ann Cotten’s (1982) multilingual poetry. The analysis of selected texts from Fremdwörterbuchsonette (2007) and Florida Räume (2010) will help us demonstrate how Cotten deploys rhetorical strategies that can be ascribed to the sphere of the neo-avant-garde and that aim at questioning the criteria presiding over the distinction (and thus over the potential hybridization) of literary genres. However, Cotten does not reject the superiority of poetry over other discourses : we will see how the criticism of obsolescence, disengagement and lyrical conservatism exhibited in the author’s verses conceals a praise of poetry as a genre still capable of conveying a form of thought, albeit to a few readers.
Keywords: Ann Cotten; Lyric Essay; Contemporary German Poetry; Experimental Poetry; Lyric